2018
DOI: 10.21037/mhealth.2018.08.01
|View full text |Cite
|
Sign up to set email alerts
|

Step-by-Step: a new WHO digital mental health intervention for depression

Abstract: The World Health Organization is developing a range of interventions, including technology supported interventions, to help address the mental health treatment gap, particularly in low and middle-income countries. One of these, Step-by-Step, is a guided, technology supported, intervention for depression. It provides psychoeducation and training in behavioural activation through an illustrated narrative with additional therapeutic techniques such as stress management (slow breathing), identifying strengths, pos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
75
0
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
3

Relationship

3
6

Authors

Journals

citations
Cited by 70 publications
(87 citation statements)
references
References 16 publications
0
75
0
2
Order By: Relevance
“…In relation to the advantages of EMH as reported by the psychiatrists in our sample, the ability of EMH to reduce the physical and societal barriers to care was the most prevalent response. Similar advantages have been reported in the literature, including the potential for greater coverage, particularly for individuals in remote areas, and the capability to anonymously access services in order to avoid stigmatization and negative public perceptions surrounding mental illness and treatment [ 7 , 36 , 37 ]. Conversely, our findings revealed that psychiatrists believed privacy, confidentiality, and security to be the most important barriers to the implementation of EMH, similar to other studies [ 30 , 38 ].…”
Section: Discussionmentioning
confidence: 55%
“…In relation to the advantages of EMH as reported by the psychiatrists in our sample, the ability of EMH to reduce the physical and societal barriers to care was the most prevalent response. Similar advantages have been reported in the literature, including the potential for greater coverage, particularly for individuals in remote areas, and the capability to anonymously access services in order to avoid stigmatization and negative public perceptions surrounding mental illness and treatment [ 7 , 36 , 37 ]. Conversely, our findings revealed that psychiatrists believed privacy, confidentiality, and security to be the most important barriers to the implementation of EMH, similar to other studies [ 30 , 38 ].…”
Section: Discussionmentioning
confidence: 55%
“…This element comes closest to what Chu and Leino (2017) considered to be peripheral aspects of psychological interventions, and what Resnicow et al (1999) described as surface adaptations. A large variety of descriptions of such adaptations has been delivered in literature, such as using culturally adapted language and metaphors (Ramaiya et al, 2017), providing culturally relevant illustrations and case examples (Verdeli et al, 2003), or using easy-to-understand texts (Carswell et al, 2018). Evidence on such adaptations has been summarised in systematic reviews (Chowdhary et al, 2014;Harper Shehadeh et al, 2016).…”
Section: Treatment Deliverymentioning
confidence: 99%
“…Die WHO hat in den vergangenen zwei Jahren eine solche Intervention zur Behandlung depressiver Symptome mit dem Namen Step-by-Step entwickelt [7].…”
Section: Mobile Selbsthilfe -Schritt Für Schrittunclassified
“…B. wird Zeina an einem Punkt weinend im Türrahmen eines Schlafzimmers dargestellt. Dabei wird nicht gesagt, ob sie den Tod eines nahen Angehörigen beweint oder sich generell abends vor dem Schlafengehen traurig fühlt, damit sich möglichst viele Personen in den Bildern wiederfinden [7]. Von großem Nutzen ist außerdem eine kürzlich eingerichtete 24-Stunden-Suizid-Hotline im Libanon.…”
Section: Zeina Und Karim Erzählen Aus Ihrem Lebenunclassified